Describing the psychosocial challeges faced by disadvantaged girl children under a specific holistic education model - Holman, Drew (My University, 2016)
The research aimed at decribing the psycho-social challenges that a specific group of disadvantaged girls (aged 15-17) face. These girls have been selected to complete their secondary schooling on a full scholarship at a private school funded by a wealthy benefactor in South Africa. The school was designed specifically for disadvantaged South African girl children who have displayed either academic or leadership excellence. This research looked at the effects of attending this school on the student’s relationships with their friends and family, culture and acculturation, and the way these challenges have impacted their functioning at the school. The school has adopted a holistic approach to education meaning that it acknowledges the importance of the students’ emotional, physical, spiritual, intellectual and psychological spheres. The research has enhanced the understanding of the psychosocial challenges the students navigate by identifying common themes within the data from which some recommendations were made. Ultimately the themes that are described will lay the foundation for further research at the institution. This study followed a qualitative research design. The population for the research was obtained by using purposive, non-probability sampling techniques. Data was gathered by making use of an interview schedule while conducting semi-structured interviews. Thematic analysis was used for analyzing the data. Key Words Descriptions, psychosocial, challenges, girl-child, holistic education model.